Aberrant pancreas adenocarcinoma in the stomach: A case report and literature review. Issue 2 (13th January 2023) - Petrauskas, Vidas; Stulpinas, Rokas; Mickys, Ugnius; Luksaite-Lukste, Raminta; Strupas, Kestutis; Poskus, Eligijus
Abstract : Rationale: Aberrant pancreatic tissue in the gastrointestinal tract is a relatively common finding. However, malignant transformation is extremely rare. Herein, we report a case of ectopic pancreatic ductal adenocarcinoma in the stomach wall. Patient concerns: A 38 year old male presented with nausea, bloating, abdominal distention and weight loss for 4 months. Diagnoses: Endoscopy of upper gastrointestinal tract was performed twice with 2 months interval and a stenotic pyloric part was observed with a suspected submucosal lesion. It was sampled both times, however the pathology findings of the mucosal biopsies were unremarkable with no identifiable neoplastic structures. CT scan and MRI was performed and showed a thickened pyloric wall with a submucosal lesion 15 × 15 mm in diameter. Blood levels of tumor markers carcinoembrionic antigen and carbohydrate antigen 19-9 were within a normal range. Interventions: Pyloric stenosis progressed and the patient underwent a Billroth type I distal gastric resection with D2 lymphadenectomy. Pathologic examination revealed a well differentiated ductal adenocarcinoma arising in the heterotopic pancreatic tissue (Heinrich type III). The resection margins and lymph nodes were free of tumor. The patient received adjuvant chemotherapy with 6 courses of XELOX. Outcomes: No disease recurrence is reported in 12 months follow-up. Lessons: Aberrant pancreatic ductal adenocarcinoma in the stomach is a rare finding, however this pathology should be included in the differential diagnosis of gastric submucosal lesion causing pyloric stenosis.